The effect of competition on the sleep patterns of elite Rugby Union players - Shearer, D. A.; Jones, M. R.; Harrington, B.; Kilduff, L. P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Rugby union is physically demanding and results in disruptions to physiological and psychological functions following competition (West et al., 2013). Insufficient recovery may compromise an individual`s physiological adaptation and/or maintenance. Halson (2008) suggested that good sleep practice in elite athletes might be the most efficacious recovery strategy. However, to date no published research has assessed sleep patterns of rugby union players following match-play. The aim of the present study was to examine sleep patterns of professional rugby union players, prior and post-match-play, to assess the influence of competition on sleep patterns. 28 male rugby union players (24.4 ± 2.9 years, 103.9 ± 12.2 kg) competed in 1 of 4 competitive home matches with similar kick-off times and training schedules prior and post-match. Players were monitored continuously using an Actiwatch® from two days prior to the match until 3 days post-match. Sleep behaviour variables measured included; time to bed, time in bed, sleep latency, time asleep, time awake, sleep efficiency, actual sleep percentage, percentage of time moving, and get up time, as previously described by Leeder et al. (2012). ANOVA showed significant differences for time to bed (F = 26.425, ç2 = 0.495, p<0.001), get up time (F = 21.175, ç2 = 0.440, p<0.001), time spent in bed (F = 10.669, ç2 = 0.283, p<0.001), time asleep (F = 8.752, ç2 = 0.245, p<0.001), and percentage of time moving (F = 4.602, ç2 =0.146p<0.05). Post-hocs revealed a significant increase for time in bed the night before the match (p<0.01; 95 % CI = 0:10 - 1:28 hrs; 9.7 ±13.5 %) compared with the reference night sleep. Furthermore, time asleep significantly decreased post-match (p<0.05; 95 % CI = -0:03 --1:59 hrs; -19.5 ± 19.8 %) compared to two nights pre-match. Results also suggested sleep efficiency reduced post-match compared to two nights pre-match, however no significant changes were observed (p>0.05). No significant changes in sleep latency, time awake, actual sleep percentage or percentage of time moving were observed on any night compared to the reference night sleep. The results demonstrate that sleep is deprived post-match which may have detrimental effects on the recovery process. The large standard deviations observed suggest a case-by-case consideration is needed for physiological and psychological monitoring.